Conservative Management of Invasive Placenta Using Combined Prophylactic Internal Iliac Artery Balloon Occlusion and Immediate Postoperative Uterine Artery Embolization. Issue 2 (May 2015) - D'Souza, Donna L.; Kingdom, John C.; Amsalem, Hagai; Beecroft, John R.; Windrim, Rory C.; Kachura, John R.
Purpose: The objective of the study was to evaluate the efficacy and safety of combined prophylactic intraoperative internal iliac artery balloon occlusion and postoperative uterine artery embolization in the conservative management (uterine preservation) of women with invasive placenta undergoing scheduled caesarean delivery. Methods: Ten women (mean age 35 years) with invasive placenta choosing caesarean delivery without hysterectomy had preoperative insertion of internal iliac artery occlusion balloons, intraoperative inflation of the balloons, and immediate postoperative uterine artery embolization with absorbable gelatin sponge. A retrospective review was performed with institutional review board approval. Outcome measures were intraoperative blood loss, transfusion requirement, hysterectomy rate, endovascular complications, surgical complications, and postoperative morbidity. Results: All women had placenta increta or percreta, and concomitant complete placenta previa. Mean gestational age at delivery was 36 weeks. In 6 women the placenta was left undisturbed in the uterus, 2 had partial removal of the placenta, and 2 had piecemeal removal of the whole placenta. Mean estimated blood loss during caesarean delivery was 1.2 L. Only 2 patients (20%) required blood transfusion. There were no intraoperative surgical complications, endovascular complications, maternal deaths, or perinatal deaths. Three women developed postpartum complications necessitating postpartum hysterectomy; the hysterectomy rate was therefore 30% and uterine preservation was successful in 70%. Conclusion: Combined bilateral internal iliac artery balloon occlusion and uterine artery embolization may be an effective strategy to control intraoperative blood loss and preserve the uterus in patients with invasive placenta undergoing caesarean delivery.